DEFINING KNOWLEDGE MANAGEMENT STRATEGY IN INDONESIAN GOVERNMENT: CASE STUDY HEAD OFFICE OF BADAN KEPEGAWAIAN NEGARA - Elin Cahyaningsih; Dieny Sukmiati; Nur Chasanah; Dana Indra Sensuse (Jurnal Sistem Informasi, 2013)
Knowledge Management (KM) became a new concept of organizational development. Many organization starts to implement knowledge management including government. First step for implementing KM in organization is defining KM strategy. This research aims to define KM strategy byKM assessment from organization vision, mission and goals using balanced scorecard (BSC) methods to find KM performance indicator in each aspect of balanced scorecard variable. This study constructs SPSS (Statistical Package for the Social Sciences) for processing and data analysis. The authors spread questionnaire at Head Office of Badan Kepegawaian Negara, Jakarta. The result of this research are KM strategies for implementing KM in Indonesian Government case study at Badan Kepegawaian Negara are monitoring program performance in order to create a working relationship and good personnel management as a learning activity for increasing organizational performance, raise up a teamwork culture within organization in to support business process in order to reach organizational performance and competitive advantage, increasing timeliness of service target achievement and standard time of customer service in order to increase organizational performance, and increasing the coordination effectiveness of program planning and budget as to increase the accountability of the organization, performance achievement and organizational performance.